Eksplorasi Enam Cara Beragama Menurut Dale Cannon Dalam Al-Qur’an - Argha Zidan Arzaqi; M. Miftaqul Miftah Lutfi (Comprehensive Journal of Islamic Studies, 2024)
Dale Cannon in his book Six Ways of Being Religious identifies six main ways of being religious. This research focuses on exploring these six ways in an Islamic context, aiming to understand Cannon's perspective on religious practice and its application in daily life. The research method used is descriptive qualitative with a literature study approach, using relevant primary and secondary sources. The results show that the six ways of religion include: (1) Sacred rites, which include the performance of worship such as prayer, fasting, zakat, and hajj; (2) Doing good and right, which emphasizes harmonious relationships with God and fellow humans; (3) Obedience, which is manifested through faith and piety; (4) Intellectual pursuits, which are efforts to gain knowledge and wisdom through reason; (5) Mystical pursuits, which involve intuitive experiences and ascetic disciplines; and (6) Samanic mediation, such as the practice of dhikr and remembering God. This approach reflects the diversity of living a spiritual and religious life, and can help understand the variations in religious practices across communities and individuals.